(untitled) (Research, Society and Development, 2022)
This current study by "The process of inclusion and education of deaf in the municipality of Humaitá-AM" historical information about the teaching process to students Deaf in the public- school of the municipality of Humaitá State of Amazonas and for a better understanding of the reader, it is divided by topics. In topic 1, he initially reports a brief historical overview of Deaf Education in Brazil where he addresses a little of the historicity of deaf education and a little bit of inclusive education, as it is quite comprehensive, since the term inclusive opens up a range of scope to be worked on, as it includes numerous issues such as racial, ethnic, gender, disabled, in short, a range of different aspects that need to be contemplated in school with acceptance and inclusion. However, our work proposes to present a part of the inclusive universe which is the inclusion of the disabled, in particular the deaf in education through Libras which is their natural language which the deaf culture calls the mother tongue or first language (L1). In topic Methodology of current, in topic 3 we present a little of the history of deaf education in the state of Amazonas, recounting its constitutive trajectory and in topic 4 we will show how the process of school inclusion of the disabled and the schooling of deaf students in the municipality of Humaitá-AM took place. to the present day. Finally, we weave the conclusions and recommendations of this work in topic 4 and the references that supported its theoretical contribution.